Design of Student Redeem Point Information System at Universitas Klabat using IoT Concept - Tombeng, Marchel Thimoty; Mandias, Green Ferry (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2026)
This study presents the design of a web-based Student Redeem Point Information System at Universitas Klabat. The system is designed to automate the Sabbath point redemption process, where students compensate for missed worship services through assigned tasks. Previously managed manually, the process was time-consuming and error-prone. Using the Prototype development model and Firebase as the backend, the new system allows students to check their points, select tasks, and upload proof of work online. Village Deans and work assigners can monitor, assign, and verify student tasks through personalized dashboards. The system enhances flexibility and accessibility by being web-based, allowing access anytime and anywhere. Testing across different user roles—students, Village Deans, and work assigners—showed successful implementation of all key functionalities. This digital approach significantly reduces administrative workload, minimizes human error, and improves efficiency in managing spiritual accountability through structured digital documentation.